Comparison of the impact of two national health and social care integration programmes on emergency hospital admissions - Marcello Morciano; Katherine Checkland; Mary Alison Durand; Matt Sutton; Nicholas Mays (BMC, 2021)
Abstract Background Policy-makers expect that integration of health and social care will improve user and carer experience and reduce avoidable hospital use. [We] evaluate the impact on emergency hospital admissions of two large nationally-initiated service integration programmes in England: the Pioneer (November 2013 to March 2018) and Vanguard (January 2015 to March 2018) programmes. The latter had far greater financial and expert support from central agencies. Methods Of the 206 Clinical Commissioning Groups (CCGs) in England, 51(25%) were involved in the Pioneer programme only, 22(11%) were involved in the Vanguard programme only and 13(6%) were involved in both programmes. We used quasi-experimental methods to compare monthly counts of emergency admissions between four groups of CCGs, before and after the introduction of the two programmes. Results CCGs involved in the programmes had higher monthly hospital emergency admission rates than non-participants prior to their introduction [7.9 (95% CI:7.8-8.1) versus 7.5 (CI: 7.4-7.6) per 1000 population]. From 2013 to 2018, there was a 12% (95% CI:9.5-13.6%) increase in emergency admissions in CCGs not involved in either programme while emergency admissions in CCGs in the Pioneer and Vanguard programmes increased by 6.4% (95% CI: 3.8-9.0%) and 8.8% (95% CI:4.5-13.1%), respectively. CCGs involved in both initiatives experienced a smaller increase of 3.5% (95% CI:-0.3-7.2%). The slowdown largely occurred in the final year of both programmes. Conclusions Health and social care integration programmes can mitigate but not prevent rises in emergency admissions over the longer-term. Greater financial and expert support from national agencies and involvement in multiple integration initiatives can have cumulative effects.